Multiple conductances are modulated by 5-hydroxytryptamine receptor subtypes in rat subthalamic nucleus neurons - Shen, Ke-Zhong (2007)
Firing patterns of subthalamic nucleus (STN) neurons influence normal and abnormal movements. The STN expresses multiple 5-hydroxytryptamine (5HT) receptor subtypes that may regulate neuronal excitability. We used whole-cell patch-clamp recordings to characterize 5HT receptor-mediated effects on membrane currents in STN neurons in rat brain slices. In 80 STN neurons under voltage-clamp (-70 mV), 5HT (30 μM) evoked inward currents in 64%, outward currents in 17%, and biphasic currents in 19%. 5HT-induced outward current was caused by an increased K(+) conductance (1.4 ± 0.2 nS) and was blocked by the 5HT(1A) antagonist WAY 100135. The 5HT-evoked inward current, which was blocked by antagonists at 5HT(2C) and/or 5HT(4) receptors, had two types of current-voltage (I-V) relations. Currents associated with the type 1 I-V relation showed negative slope conductance at potentials < -110 mV and were occluded by Ba(2+). In contrast, the type 2 I-V relation appeared linear and had positive slope conductance (0.64 ± 0.11 nS). Type 2 inward currents were Ba(2+)-insensitive, and the reversal potential of -19 mV suggests a mixed cation conductance. In STN neurons in which 5HT evoked inward currents, 5HT potentiated burst firing induced by N-methyl-D-aspartate (NMDA). But in neurons in which 5HT evoked outward current, 5HT slowed NMDA-dependent burst firing. We conclude that 5HT receptor subtypes can differentially regulate firing pattern by modulating multiple conductances in STN neurons.